Global Disruptions and SME Resilience: A Framework for Strategic Adaptation - Munna, Md Shariful Alam (My University, 2025)
Abstract In today's interconnected global economy, small and medium enterprises (SMEs) face increasing vulnerability to systemic disruptions. This thesis examines the impact of two major global disruptions: the COVID-19 pandemic and the Russia-Ukraine war on SMEs, specifically focusing on Bangladesh's ready-made garment (RMG) sector. This study concentrates on these two transformative crises that have reshaped global business operations. The research explores how SMEs navigate compound challenges including supply chain disruptions, energy price volatility, and cascading economic shocks. The study employs Dynamic Capabilities Theory and the PESTEL framework to analyze how these global disruptions influence SME business strategies. Through qualitative analysis of survey and interview data, the research examines SME vulnerabilities. Subsequently, it proposes a tailored hybrid risk management framework designed specifically for resource-constrained enterprises. The findings reveal that SMEs face distinct challenges when confronting pandemic-induced restrictions and war-related supply disruptions. These challenges include limited financial reserves, inflexible supply chains, insufficient market intelligence, and inadequate crisis preparedness. Moreover, the research identifies a disruption stacking phenomenon whereby SMEs recovering from COVID-19 impacts simultaneously encounter war-induced cost pressures, thereby overwhelming their adaptive capacities. Furthermore, the study demonstrates that SMEs can enhance their resilience through specific strategies. These include implementing scenario planning for multiple crisis situations, diversifying supply networks beyond traditional sources, and monitoring regulatory changes related to health protocols and trade sanctions. Additionally, investing in information systems that track pandemic trends and conflict-related market developments proves beneficial. Consequently, the research proposes a Risk Management Resilience Framework comprising three stages: risk identification, risk assessment, and risk response. This framework is specifically calibrated to address the dual challenges of health crises and geopolitical conflicts affecting SMEs. The thesis contributes both theoretical and practical insights. Theoretically, it extends strategic management theories to SME responses during compound global disruptions. Practically, it provides SMEs with evidence-based guidance for managing pandemic-style disruptions, addressing war-induced supply chain volatility, and capitalizing on crisis-generated opportunities. The study offers policymakers and development organizations empirical evidence supporting targeted crisis management assistance for SMEs in disruption-prone economies. Ultimately, this research demonstrates that SMEs must proactively and systematically address challenges arising from interconnected global crises such as pandemics and regional conflicts. Therefore, by integrating these specific global disruptions into their strategic planning processes, SMEs can enhance their operational agility, improve long-term viability, and strengthen overall economic stability.
Keywords: fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development